Propagation potentials of genotypes and different physiological ages of stem cuttings in Jatropha curcas L. - A K M, Aminul Islam; Yaakob, Zahira; Anuar, Nurina; Osman, Mohamad (Canadian Center of Science and Education, 2010)
Propagation potentials of stem cuttings of different physiological ages and genotypes of physic nut (Jatropha curcas L.) were studied at UKM, Malaysia. Stem cuttings of the different physiological ages (hardwood, semi hardwood and soft wood) taken from five selected genotypes of Jatropha were planted in soil media (top soil). Data were collected on the attributes of the stem cuttings and then analyzed using computer based software, SAS, version 9.01, (2008). The study showed significant variability in shoot and root development and growth of shoots of the three physiological ages of cuttings and five genotypes. Semi hardwood stem cuttings had lower days to opening of new bud and shooting (4.8 and 11.7 d, respectively) as well as higher percentage of sprouted and rooted cuttings of 100% and 98.5%, respectively. Soft wood cuttings took more days to opening of new bud and shoot development in all five genotypes. Soft wood cuttings also showed lower percentage of rooted cuttings. Semi hard wood cuttings proved to be more suitable for the vegetative propagation of Jatropha curcas through stem cutting, which gave more than 98% success. Genotypic differences were observed in shooting and rooting of Jatropha. Genotype JC 14 performed better in all three types of cutting compared to other four genotypes.